2002
DOI: 10.1116/1.1445166
|View full text |Cite
|
Sign up to set email alerts
|

Electron field emission from hydrogen-free amorphous carbon-coated ZnO tip array

Abstract: Articles you may be interested inImproved conductivity of aluminum-doped ZnO: The effect of hydrogen diffusion from a hydrogenated amorphous silicon capping layer Noise characteristics of emission current from conductive diamond-like carbon thin films coating on cone shaped silicon field emitters Enhanced electron field emission from hydrogen-free amorphous carbon ͑a-C͒ films deposited on ZnO-tip-array-coated Si substrates was studied. Both the ZnO tip array and the a-C films were deposited by filtered arc dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…It was found that the dimensions of ZnO nanowires could be controlled from 25 to 80 nm by the varying the ZnCl 2 concentration [121]. Notably, Cl − ions became adsorbed preferentially on the Zn-terminated (0001) planes of ZnO, which eventually hindered the growth along the polar axis, giving rise to platelet-like crystals [124], even though the anions are not considered as reactants according to equations (11) and (12). Even when other zinc salts rather than ZnCl 2 were used as precursors, the Cl − could also come from the supporting electrolyte KCl [125].…”
Section: Electrodepositionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the dimensions of ZnO nanowires could be controlled from 25 to 80 nm by the varying the ZnCl 2 concentration [121]. Notably, Cl − ions became adsorbed preferentially on the Zn-terminated (0001) planes of ZnO, which eventually hindered the growth along the polar axis, giving rise to platelet-like crystals [124], even though the anions are not considered as reactants according to equations (11) and (12). Even when other zinc salts rather than ZnCl 2 were used as precursors, the Cl − could also come from the supporting electrolyte KCl [125].…”
Section: Electrodepositionmentioning
confidence: 99%
“…It has also been suggested that when using Zn(NO 3 ) 2 as the precursor, reduction of NO 3 − at the cathode could also provide a possible source of OH − [122], as indicated by equation (12). In any case, the ratio between the OH − generation rate at the cathode and the Zn 2+ diffusion rate to the cathode was proposed to be the major parameter in the electrodeposition of ZnO nanowires [123].…”
Section: Electrodepositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of zinc oxide (ZnO) material, specifically ZnO nanorod (NR) or nanowire (NW) morphology, are continuously performed because of numerous applications of ZnO NRs in many fields of science, especially in branches of electronics, optoelectronics, electrochemistry, and electromechanics [1][2][3][4][5][6]. Some examples of these applications are ultraviolet (UV) lasers [7,8], light-emitting diodes [9], field-emission devices [10][11][12], high-performance nanosensors [13,14], solar cells [15][16][17][18], piezoelectric nanogenerators [19][20][21], and nano-piezotronics [22,23]. ZnO NR is one of the most frequently used forms of nanostructures because of its ease of fabrication by relatively less complicated methods.…”
Section: Introductionmentioning
confidence: 99%
“…Once doped, they display new properties, e.g., electrical conductivity, magnetic, magneto-optical, photocatalytic, antibacterial and optical [ 74 , 161 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 ]. At present, various ZnO nanostructures are being used in attempts to produce a new generation of light-emitting diodes [ 233 , 234 ], lasers [ 235 ], field emission devices [ 236 , 237 ], memory carriers [ 238 , 239 ], solar cells [ 240 , 241 , 242 , 243 , 244 , 245 , 246 ], liquid crystals [ 247 ], polymer nanocomposites [ 248 , 249 , 250 , 251 ], food packaging materials [ 252 , 253 , 254 , 255 , 256 , 257 , 258 ], transparent ultraviolet light absorbers in unplasticised polymers [ 259 ], catalysts [ 260 ], photoluminescent NPs [ 261 ], photocatalysts ...…”
Section: Introductionmentioning
confidence: 99%